Comparative Analysis of Financial Ratio Before and During the Covid-19 Pandemic in Retail Trade Companies in Indonesia Before and During the Covid-19 Pandemic - SIPAHUTAR, Robinson; PURBA, Betniar (PT Keberlanjutan Strategis Indonesia, 2024)
This study aims to determine the financial performance of retail trading companies listed on the Indonesia Stock Exchange before and during the first year of the COVID-19 pandemic in 2020 until early 2021. The financial ratios used are the current ratio, debt to asset ratio, debt to equity ratio. , total assets turnover, and return on equity. The population in this study are companies listed on the Indonesia Stock Exchange. Sampling was done by purposive sampling method. The population is 26 retail trading companies listed on the Indonesia Stock Exchange in 2020. A sample of 24 companies that have published their financial statements 2020. The data analysis method used is the paired sample t-test and the Wilcoxon signed rank test, which were previously tested normality. The results of the analysis show that the company's profitability during the COVID-19 pandemic when viewed from ROA, ROE and PM can be said to be unhealthy, because the company's average profitability is below the industry standard ratio value. Meanwhile, the company's liquidity during the COVID-19 pandemic when viewed from the CR, DER and DAR can also be said to be unhealthy. This can be seen from the average ratio value, far from the industry standard ratio value